Cerebrospinal fluid, plasma, and saliva in the BioFIND study: Relationships among biomarkers and Parkinson's disease Features. Issue 2 (4th December 2017) - Goldman, Jennifer G.; Andrews, Howard; Amara, Amy; Naito, Anna; Alcalay, Roy N.; Shaw, Leslie M.; Taylor, Peggy; Xie, Tao; Tuite, Paul; Henchcliffe, Claire; Hogarth, Penelope; Frank, Samuel; et al.
ABSTRACT: Objective: Examine relationships among neurodegenerative biomarkers and PD motor and nonmotor symptoms. Background: CSF alpha‐synuclein is decreased in PD versus healthy controls, but whether plasma and saliva alpha‐synuclein differentiate these groups is controversial. Correlations of alpha‐synuclein among biofluids (CSF, plasma, saliva) or biomarkers (eg, beta‐amyloid, tau [total, phosphorylated]) are not fully understood. The relationships of these biomarkers with PD clinical features remain unclear. Methods: BioFIND, a cross‐sectional, observational study, examines clinical and biomarker characteristics in moderate‐advanced PD and matched healthy controls. We compared alpha‐synuclein concentrations across diagnosis, biofluids, and CSF biomarkers. Correlations of CSF biomarkers and MDS‐UPDRS, motor phenotype, MoCA, and rapid eye movement sleep behavior disorder questionnaire scores in PD were examined. Results: CSF alpha‐synuclein was lower in PD versus controls ( P = .01), controlling for age, gender, and education. Plasma and saliva alpha‐synuclein did not differ between PD and controls, and alpha‐synuclein did not significantly correlate among biofluids. CSF beta‐amyloid1‐42 was lower in PD versus controls ( P < .01), and correlated weakly with MoCA recall scores ( r = 0.23, P = .02). CSF alpha‐synuclein was lower in the postural instability/gait difficulty phenotype than other motor phenotypes ( P < .01). No CSF biomarkers predicted or correlated with total motor or rapid eye movement sleep behavior disorder scores. CSF alpha‐synuclein correlated with beta‐amyloid1‐42, total‐tau, and phosphorylated‐tau ( r = 0.41, 0.81, 0.43, respectively; P s < .001). Conclusion: Lower CSF alpha‐synuclein is associated with diagnosis and motor phenotype in moderate‐advanced PD. Plasma and saliva alpha‐synuclein neither correlate with CSF alpha‐synuclein, nor distinguish PD from controls. CSF beta‐amyloid1‐42 remains a potential biomarker for cognitive impairment in PD. © 2017 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.